Leucasin - Induced Cytoplasmic Membrane Damage in Staphylococcus aureus - S. Meghashr; S. Gopal (International Journal of Phytomedicine, 2012)
Leucasin is one of the active antimicrobial principle of Leucas aspera. The effect of this compound and other antibacterial agents with known mechanisms of action upon the cytoplasmic membrane integrity of Staphylococcus aureus was investigated by comparing scanning electron microscopy (SEM) and potassium loss profiles from bacterial cell suspensions. The minimum inhibitory concentrations (MICs) of leucasin, novobiocin - the bacteriostatic antibiotic and penicillin G – the bactericidal antibiotic against S. aureus (ATCC 12600) were determined as 35 μg/ml, 55 ng/ml and 40 ng/ml respectively. The morphology of S. aureus was impaired, when treated with leucasin showing mucilaginous mass, which could lead to the impairment in cell division, as observed under SEM. When S. aureus were suspended in potassium free media containing 35 μg/ml leucasin, a 100 fold decrease in viability was observed after 12 h. Potassium loss assay revealed that S. aureus treated with 35 μg/ml leucasin lost 17% more potassium than untreated control populations whereas, cells treated with 40 ng/ml of penicillin G exhibited 9% increase in potassium loss and 55 ng/ml of novobiocin had no effect on potassium loss. This data may be attributed to either direct damage to the cytoplasmic membrane or indirect damage affected through autolysis/weakening of the cell wall and consequent osmotic lysis.